Cost Efficiency of Banking Sector of Bangladesh: Evidence Using the Stochastic Frontier Analysis - Hassan, Md Hashibul; Hassan, Mahmudul (Asian Journal of Empirical Research, 2018)
Banking industry dominates the financial sector of Bangladesh with an approximate share of 74% of the total intermediation. In recent years, this industry is at high risk due to supervision gaps, overcapacity and market distortions. Therefore, measuring the efficiency of the banking industry is critically important to identify poor banks and bring stability by concentrating on their performance. This study employs single stage stochastic frontier analysis (SFA) to measure the cost efficiency in the Bangladeshi banking sector during the 2011-2015 period. Five different stochastic models are used across the 35 sample banks. Evidence suggests that the mean cost efficiency found in the Bangladeshi banking sector is 88.50%. The mean efficiency is lower among the state-owned banks than conventional (private) commercial banks and Islamic Sariah banks. From the analysis, it seems that there is a low technological advancement in the banking sector during 2011-2015. Further, the analysis indicates that non-performing loans have a significant effect in reducing the overall cost efficiency among the banks.